2004
DOI: 10.1111/j.1526-4610.2004.04141.x
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Hypothalamic and Brainstem Activation in Hemicrania Continua

Abstract: This study demonstrated activations of various subcortical structures, in particular the posterior hypothalamus and the dorsal rostral pons. If posterior hypothalamic and brainstem activation are considered as markers of trigeminal autonomic headaches and migrainous syndromes, respectively, then the activation pattern demonstrated in hemicrania continua mirrors the clinical phenotype, with its overlap with trigeminal autonomic headaches and migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
2
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(182 citation statements)
references
References 75 publications
(172 reference statements)
13
163
2
4
Order By: Relevance
“…There are few reports that point to brainstem structures, such as ventrolateral midbrain, rostral-dorso part of pons and bulb-pons junction, involved in the pathophysiopathy of hemicrania continua. 5 MRI and positron emission tomography (PET) studies have shown that the grayish substance in the posteriorinferior hypothalamus is activated during trigemino autonomic cephalalgias 6 . On the other hand, clinical, PET and deep cerebral stimulation studies suggest that the rostral portion of the brainstem is essential to migraine pathophysiology, with emphasis on the role of periaqueductal gray substance contralateral to the pain episode 7 .…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports that point to brainstem structures, such as ventrolateral midbrain, rostral-dorso part of pons and bulb-pons junction, involved in the pathophysiopathy of hemicrania continua. 5 MRI and positron emission tomography (PET) studies have shown that the grayish substance in the posteriorinferior hypothalamus is activated during trigemino autonomic cephalalgias 6 . On the other hand, clinical, PET and deep cerebral stimulation studies suggest that the rostral portion of the brainstem is essential to migraine pathophysiology, with emphasis on the role of periaqueductal gray substance contralateral to the pain episode 7 .…”
Section: Discussionmentioning
confidence: 99%
“…These headache syndromes are compared with other short-lasting headache disorders, such as hypnic headache, and a chronic headache syndrome with milder autonomic features such as hemicrania continua. Recent imaging data, however, place hemicrania continua nearer to the TACs [28] and future work will probably do the same with hypnic headache. Idiopathic stabbing headache, cough headache, exertional headache, sexual headache and trigeminal neuralgia are not part of these syndromes as these short-lasting disorders have no autonomic component [16,38].…”
Section: Arne Maymentioning
confidence: 94%
“…Melatonin in particular is a marker of the circadian system and a blunted nocturnal peak melatonin level and complete loss of circadian rhythm have been reported in cluster headache patients [51]. Recently, using functional and structural imaging, a significant structural difference in grey matter density, a Ôlesion' coinciding with the inferior posterior hypothalamus, was found in cluster headache [33,45] and Hemicrania continua [28], but not in migraine patients [30] when compared to healthy controls. Given that many of the basic features of SUNCT are shared by cluster headache and paroxysmal hemicrania, the question arises whether a shared pathophysiological basis exists, which could possibly be visualized through similar cerebral activation patterns.…”
Section: The Pathophysiological Puzzlementioning
confidence: 95%
“…Subsequently, it was shown that this hypothalamic area is also activated during short-lasting, unilateral, neuralgiform headache attacks with conjunctival injection and tearing (SUNCT), 43,44 paroxysmal hemicrania 45 and hemicrania continua. 46 Despite this, a second study found no activation in the hypothalamus in hemicrania continua in a single patient without cranial autonomic features. 47 For DBS the electrode is usually implanted stereotactically in the left posterior hypothalamus/anterior periventricular region of the triangle of Sano, according to the co-ordinates published.…”
Section: Defining the Target Pointmentioning
confidence: 99%